229k views
5 votes
Which expression is equivalent to the expression

Which expression is equivalent to the expression-example-1
User UtopiaLtd
by
5.1k points

2 Answers

3 votes
This simplifies to -3c, with the constraint that c should not be equal to 1/2.
User IftekharDani
by
5.5k points
5 votes

The trick with these is to just try a number. c=1

( (6+3)/(-4+2) ) / ( (2+1)/(4-2) ) = (9/-2)/(3/2)) = -3

Last choice.

If there was a none of the above we'd have to do the algebra, which is straightforward:


\frac{ (6c^2+3c)/(-4c+2) } { (2c + 1)/(4c - 2) }=(6c^2+3c)/(-4c+2) \cdot (4c - 2)/(2c + 1)


=(4c-2)/(-4c+2)\cdot(6c^2+3c)/(2c + 1)


=(-1)\cdot(3c(2c+1))/(2c + 1)


=-3c
User Akshay Paliwal
by
5.4k points